2010
DOI: 10.1111/j.1439-0531.2010.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Summer Anoestrus in Buffalo – A Review

Abstract: The present review addresses summer anoestrus in buffaloes. The condition is a major impediment in the improvement of reproductive as well as productive efficiency in buffalo. Factors affecting summer anoestrus include environment, nutrition and management. The environmental factors especially longer day length and increased temperature with high humidity pre-dispose to the condition when the nutritive status of buffaloes is poor. Buffaloes with summer anoestrus fail to exhibit oestrus as a result of aberratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 53 publications
(57 reference statements)
1
59
0
1
Order By: Relevance
“…*P < 0.05, **P < 0.01, ***P < 0.001. cholesterol level observed in group FR may be because of the higher physical activity performed by the heifers kept on pasture. Cholesterol, a precursor molecule needed in the biosynthetic pathway of steroid hormones, is related to the ovarian functional activity (Das and Khan, 2010). The physiological levels observed by other authors in adult cyclic female buffaloes ranged between 2.08 and 3.78 mmol/l (Campanile et al, 1998;Das and Khan, 2010), whereas lower values were found in acyclic Murrah buffalo heifers (Anand and Prakash, 2008), and even lower levels (1.80 mmol/l), similar to those observed in this study, were observed by Borghese et al (2010) in a study on buffalo young bulls.…”
Section: Behaviour and Puberty Of Buffalo Heifersmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01, ***P < 0.001. cholesterol level observed in group FR may be because of the higher physical activity performed by the heifers kept on pasture. Cholesterol, a precursor molecule needed in the biosynthetic pathway of steroid hormones, is related to the ovarian functional activity (Das and Khan, 2010). The physiological levels observed by other authors in adult cyclic female buffaloes ranged between 2.08 and 3.78 mmol/l (Campanile et al, 1998;Das and Khan, 2010), whereas lower values were found in acyclic Murrah buffalo heifers (Anand and Prakash, 2008), and even lower levels (1.80 mmol/l), similar to those observed in this study, were observed by Borghese et al (2010) in a study on buffalo young bulls.…”
Section: Behaviour and Puberty Of Buffalo Heifersmentioning
confidence: 99%
“…They are of particular importance for meat and milk production in tropical and subtropical countries because of their ability to adapt to harsh environmental conditions (Das and Khan, 2010;Yindee et al, 2011). There are two distinct types, the riverine and swamp types.…”
Section: Introductionmentioning
confidence: 99%
“…Buffalo is one of the most important livestock species populated largely in tropical and sub-tropical countries (Das and Khan, 2010). Dairy buffalo production has been a tradition in Asia especially in south Asian countries like Bangladesh, India, Pakistan and Afghanistan.…”
Section: Introductionmentioning
confidence: 99%